Haplotype-Based Analysis of KIR-Gene Profiles in a South European Population—Distribution of Standard and Variant Haplotypes, and Identification of Novel Recombinant Structures - Cisneros, Elisa; Moraru, Manuela; Gómez-Lozano, Natalia; Muntasell, Aura; López-Botet, Miguel; Vilches, Carlos (Frontiers in Immunology, 2020)
Inhibitory Killer-cell Immunoglobulin-like Receptors (KIR) specific for HLA class I molecules enable human natural killer cells to monitor altered antigen presentation in pathogen-infected and tumour cells. KIR genes display extensive copy-number variation and allelic polymorphism. They organize in a series of variable arrangements, designated KIR haplotypes, which derive from duplications of ancestral genes and sequence diversification through point mutation and unequal crossing-over events. Genomic studies have established the organization of multiple KIR haplotypes – many of them are fixed in most human populations, whereas variants of those have less certain distributions. Whilst KIR-gene diversity of many populations and ethnicities has been explored superficially (frequencies of individual genes and presence/absence profiles), less abundant are in-depth analyses of how such diversity emerges from KIR-haplotype structures. We characterize here the genetic diversity of KIR in a sample of 414 Spanish individuals. Using a parsimonious approach, we manage to explain all thirty-eight observed KIR-gene profiles by homo- or heterozygous combinations of six fixed centromeric and telomeric motifs; of six variant gene arrangements characterized previously by us and others; and of two novel haplotypes never detected before in Caucasoids. Associated to the latter haplotypes, we also identified the novel transcribed KIR2DL5B*0020202 allele, and a chimeric KIR2DS2/KIR2DL3 gene (designated KIR2DL3*033) that challenges current criteria for classification and nomenclature of KIR genes and haplotypes.